Pyogenic liver abscess in non‐liver cancer patients and liver cancer patients treated with TACE: Etiological characteristics, treatment, and outcome analysis - Yi‐Ming Liu; Yan‐Qiao Ren; Song‐Lin Song; Chuan‐Sheng Zheng (Kaohsiung Journal of Medical Sciences, 2023)
Abstract Clinical, laboratory, and microbiological features, clinical outcomes, and pyogenic liver abscess (PLA) prognosis evaluation in non‐liver cancer (Non‐LC) and liver cancer patients treated with transarterial chemoembolization (TACE, LC‐TACE). Clinical data of 48 consecutive PLA patients from January 2016 to December 2020 were retrospectively analyzed. Mortality between two PLA patient groups were compared, and mortality risk factors were evaluated. A total of 48 PLA patients (31 males and 17 females) from January 2016 to December 2020 met the study's inclusion criteria. There were 32 and 16 patients in the Non‐LC and LC‐TACE groups, respectively. Positive pus culture rate in the Non‐LC group was 87.5% and positive pus culture rate in LC‐TACE group was 81.3%. In the Non‐LC group, 28 patients improved after treatment, 1 patient did not improve, and 3 patients died during hospitalization, with a 9.4% mortality rate. In the LC‐TACE group, nine patients improved after treatment, three patients did not improve, and four patients died during hospitalization, with a 25% mortality rate. The Non‐LC group cure time was 37.4 ± 23.1 days, while the LC‐TACE group was 91.5 ± 49.7 days. PLA of the Non‐LC group and the LC‐TACE group were different in terms of pathogenic bacteria and cure time, and so on. A more comprehensive treatment should be considered for PLA after TACE.